Study of p-type silicon MOS capacitors at HL-LHC radiation levels through irradiation with a cobalt-60 gamma source and a TCAD simulation. (30th June 2021) - Asenov, P.; Assiouras, P.; Boziari, A.; Filippou, K.; Kazas, I.; Kyriakis, A.; Loukas, D.; Morozzi, A.; Moscatelli, F.; Passeri, D.
Abstract: During the era of the High Luminosity LHC (HL-LHC) the devices in its experiments will be subjected to increased radiation levels with high fluxes of neutrons and charged hadrons, especially in the inner detectors. A systematic program of radiation tests with neutrons and charged hadrons is being carried out by the CMS and ATLAS Collaborations in view of the upgrade of the experiments, in order to cope with the higher luminosity at HL-LHC and the associated increase in the pile-up events and radiation fluxes. In this work, results from a complementary radiation study with 60 Co-γ photons are presented. The doses are equivalent to those that the outer layers of the silicon tracker systems of the two big LHC experiments will be subjected to. The devices in this study are MOS capacitors fabricated on the float-zone oxygenated p-type silicon wafer. The results of CV measurements on these devices are presented as a function of the total absorbed radiation dose following a specific annealing protocol. The measurements are compared with the results of a TCAD simulation.